Analysis of Lexical of English Spoken by Non-Native Speakers in British Television Series Mind Your Language Session 1 - Muhammad Ihsan; Catur Kepirianto (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2022)
In language, ambiguity is often considered a problem. Ambiguity can be found in every aspect of language whether it is written or spoken. Research in terms of ambiguity mostly found in written language, but this study conducted using spoken data. In this research, the ambiguity that is going to be studied is an ambiguity spoken by Non-native English speaker in a humoristic way. Lexical ambiguity is usually caused by homonymy and polysemy. This research aims to describe the ambiguity in the British television series Mind Your Language Season 1 and the writer focus on the lexical ambiguity and contextual meaning. The type of this research is descriptive qualitative. The technique of collecting the data is note-taking technique. The writer describes all possible meanings from the ambiguous jokes by analyzing the contextual meaning. This study conducted to find types of lexical ambiguity used by non-native English and described all possible meanings from the ambiguous jokes within the context. There are two lexical ambiguities found in this data, polysemy and homonymy. The writer found 51 words considered as lexical ambiguity. From 51 words, 15 words were classified as polysemy and 36 as homonymy. In homonymy, there are 18 words categorized in both homonyms and homophones. By analyzing the contextual meaning, the writer reveals the correct interpretation and intention of the ambiguous words. The writer also found the reason why the jokes are considered as lexical ambiguity. Finally, the writer reveals the type of lexical ambiguity used by non-native English.Keywords: ambiguity; contextual meaning; lexical ambiguity; polysemy; homonymy